PENGARUH HEDONIC MOTIVE & VISUAL MERCHANDISING TERHADAP SHOPPING LIFESTYLE & IMPULSE BUYING DI MATAHARI DEPARTMEN STORE LOMBOK EPICENTRUM MALL - Ni Made Dwi Desyantari Putri (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research is aimed at examining and analyzing the effect of hedonic motive on shopping lifestyle, the effect of visual merchandising on shopping lifestyle, the effect of hedonic motive on impulse buying, the effect of visual merchandising on impulse buying, the effect of shopping lifestyle on impulse buying, this research quantitative study with the population of all men and women who had ever shopped in Matahari Department Store Lombok Epicentrum Mall in Mataram. The data were analyzed with structural equation model. The research showed that hedonic motive has sigificant effect on shopping lifestyle, visual merchandising has significant effect on shopping lifestyle. hedonic motive has sigificant effect on impulse buying, visual merchandising has significant effect on impulse buying. Keywords: hedonic motive, visual merchandising, shopping lifestyle, Impulse buying